Hybrid Quality Management Model in Vocational Education: Strengthening National Standards with International Principles - Sinta Qoriatul Monica; Siti Aimah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
As the demands of vocational education globalization and the international industry’s need for competitive graduates continue to rise, the independent implementation of National Education Standards is deemed insufficient to fully ensure adaptive and sustainable quality management, particularly in vocational high schools operating as Regional Public Service Agencies. This study aims to critically examine and evaluate the implementation of the Hybrid Quality Management Model as an integrated approach that combines National Education Standards with international quality management principles based on ISO 9001:2015 in the quality management of vocational education at vocational high schools. Using a qualitative approach with a case study design, this research collected data from key informants, including school principals, quality assurance teams, teachers, Regional Public Service Agency administrators, and industry partners through in-depth interviews, observation of quality assurance processes, and analysis of official documents, with data validity ensured through triangulation and thematic analysis. The research findings reveal the existence of two distinct quality assurance practices: compliance with National Education Standards, which focuses on administrative compliance, and process-based quality management aligned with ISO 9001:2015, as evidenced by the implementation of standard operating procedures, ongoing internal audits, and corrective action mechanisms. This study contributes novelty to the literature on educational quality management by proposing the Hybrid Quality Management Model as a new conceptual approach that systematically positions international quality management principles as structural reinforcements of the National Education Standards, rather than merely as supplements or parallel systems.